Local government and urban governance in Europe - Silva, Carlos Nunes; Buček, Ján (Springer, 2017)
This book discusses innovative responses and reforms developed in critical areas of urban governance in European countries. It examines the impact of European Union?s policies on the urban agenda and on local governance, and the impact of the transition to democracy in Central and in Southern Europe on local self-government systems. The book is divided into three parts: i) Crisis, Reform and Innovation in Local Government; ii) EU Policies, the Urban Agenda and Local Governance; and iii) Citizen Participation in Local Government. Providing an extensive and updated overview of key challenges in the governance of cities in Europe, the book will be of interest to students and researchers in the broader field of urban studies, and for policy-makers, especially those engaged in urban governance in European countries.
Keywords: Local government -- Europe.; Public administration -- Europe.; Municipal government -- Europe.; Europe.; elektronické knihy; electronic books